2017
DOI: 10.1021/acsami.7b01766
|View full text |Cite
|
Sign up to set email alerts
|

Hybridized C–O–Si Interface States at the Origin of Efficiency Improvement in CNT/Si Solar Cells

Abstract: Despite the astonishing values of the power conversion efficiency reached, in just less than a decade, by the carbon nanotube/silicon (CNT/Si) solar cells, many doubts remain on the underlying transport mechanisms across the CNT/Si heterojunction. Here, by combining transient optical spectroscopy in the femtosecond timescale, X-ray photoemission, and a systematic tracking of I-V curves across all phases of the interlayer SiO growth at the interface, we grasp the mechanism that adequately preserves charge separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Before our 2012 report on the early progress in this field, and the recent efficiency and active area records, the first report of carbon nanotube–silicon heterojunctions being used specifically for solar cells was by Wei et al in 2007 . The overall power conversion efficiency (PCE) of Wei et al's device was around 1.3% but, as can be seen in Figure 1 and in Table S1 of the Supporting Information, very rapid efficiency gains have been made since then, as might be expected for an architecture based on the already mature field of silicon photovoltaics (PV). However, there is still significant room for improvement in the maximum efficiency of proof‐of‐principle laboratory cells.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Before our 2012 report on the early progress in this field, and the recent efficiency and active area records, the first report of carbon nanotube–silicon heterojunctions being used specifically for solar cells was by Wei et al in 2007 . The overall power conversion efficiency (PCE) of Wei et al's device was around 1.3% but, as can be seen in Figure 1 and in Table S1 of the Supporting Information, very rapid efficiency gains have been made since then, as might be expected for an architecture based on the already mature field of silicon photovoltaics (PV). However, there is still significant room for improvement in the maximum efficiency of proof‐of‐principle laboratory cells.…”
Section: Introductionmentioning
confidence: 97%
“…However, in direct contradiction is a theoretical study by Imran and Butt comparing detailed physics‐based modeling of nanomaterial–insulator–semiconductor photovoltaics to the experimental results of Jia et al and showing good correlation between the predicted and experimentally measured variations in efficiency with oxide thickness, yielding a peak in efficiency at around 12 Å (estimated by comparison of oxygen and silicon Auger signals) . In relevant related work, XPS studies by Pintossi et al have shown that the stoichiometry of the oxide can be critical to performance, and recent work from Ponzoni et al has suggested the intriguing possibility of direct COSi bond formation between the nanotubes and the silicon during the sequence of treatments that follow deposition of the nanotubes on the surface (though this is currently only a theoretical model—the experimental evidence is limited to an interpretation of peak fitting to the high‐energy components of the C1s XPS peak). If it is indeed true that COSi bonds are formed, this would have broad implications for the carbon nanotube–silicon interface ranging far beyond their use in photovoltaics.…”
Section: Introductionmentioning
confidence: 99%
“…One prerequisite for engineering SWNT based-optical devices is the understanding of their photophysics on an ultrafast timescale. For instance, tracking ultrafast charge transfer processes between different SWNTs or SWNT-Si heterojunctions can provide important information for designing SWTN-based photovoltaic devices 8 , 9 . Furthermore, the ultrafast dynamics of SWNTs offers reliable optical switching mechanism for laser mode-locking 3 , 4 , 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The energy difference between the excited states sampled by the current in {Mn 4 } (27 μeV) and in {Co 4 } (100 μeV at B = 8 T) is orders of magnitude smaller than other processes known to cause RTS in CNT devices [43][44][45]. Note that these transitions do not involve spin flips, as those would require comparably large energies, since states with different spin configuration lie ∼2 orders of magnitude higher in energy (see Sec.…”
Section: Theoretical Modelmentioning
confidence: 96%